Preliminary Survey on Spider Fauna of DMZ Areas in Korea - 임문순; Sue Yeon Lee; 김영진; 정명표; 김승태 (Journal of forest and environmental science , 34(3), 2018)
Spider fauna of Demilitarized Zone (DMZ) and adjacent areas in Korea was surveyed in 2001-2003, 2013-2015, and 2017. Total of 34 surveyed areas across 10 provinces were divided into four main regions (east coast, mid-east mountain, midland, and west coast areas) in accordance with administrative districts and topography. Total of 273 species of 145 genera in 32 families were identified from 10,886 collected spiders. In conclusion, the spider fauna in the DMZ is 281 species of 147 genera in 32 families with 162 species of 99 genera in 23 families in the previous reports. This corresponds to about 37.6% of the Korean spiders as of 2015. The species richness among surveyed localities was ranged 45 species to 92 species. The species richness of each taxon is high in Araneidae, Salticidae, Linyphiidae and Theridiidae. Habitat generalists were 22 species and habitat specialists were 69 species. The 143 species were web builders and 130 species were wanderers by the outlined life style. In DMZ spiders, only 7 species, Thymoites ulleungensis, Arcuphantes pennatus, Lycosa coreana, Allagelena koreana, Cybaeus mosanensis and Cybaeus triangulus, Kishidaia coreana, were recognized as Korean endemic. Five species, Scytodes thoracica, T. ulleungensis, Lycosa labialis, Takeoa nishimurai, and Phrynarachne katoi, are rare species with a trend of decreasing density in recent years. Araneus rotundicornis has been discovered for the first time since its first report. This study may be useful in the conservative management and will contribute to knowledge of the distribution and biogeography of DMZ areas in the future. KCI Citation Count: 0